THE ROLE AND DISADVANTAGES OF ARTIFICIAL INTELLIGENCE IN EDUCATIONAL INSTITUTIONS (Modern education and development, 2025)
This article aims to present how artificial intelligence can be used in the development of education, highlighting the benefits and risks associated with its use, as well as the shortcomings in the use of artificial intelligence in educational processes in Uzbekistan. This article discusses the concept of artificial intelligence and its various types, advantages, and disadvantages of artificial intelligence used in education. Artificial intelligence in educational processes in Uzbekistan.